#TITLE_ALTERNATIVE# - AKBAR (NIM : 15109037), AIDIL
Ionosphere refraction is one source of Global Navigation Satellite System (GNSS) data errors.with it’s greates influence is on signal speed which affects the error of position measurement into tens of meters The amount of influence of inospheric refraction is affected by Total Electron Content (TEC) in the ionosphere. TEC is one of the paremeters to study the physical characteristic of ionosphere that need to be studied it's spatial and temporal dynamic. This dynamic is influenced by solar activity. This research will study and discuss the temporal characteristic of TEC from the Internasion GNSS Service (IGS) station of Badan Informasi Geospasial (BIG) from January 2010 to December 2012 and find it’s correlation with Solar Flux using method of Pearson Correlation. Based on this research can observe that TEC value change every day, every month, and every year (temporal variation) which affected by sun’s activity and position relative to the earth. The minimum activity occur in the morning between 04:00 am until 06:00 am with TEC value less than 20 TECU and it’s maximum between 02:00 pm until 03:00 pm with TEC value more than 40 TECU. The ionosphere activity show the escalation from 2010 to 2012. Summer solstice is the season with the minimum of ionosphere activity and equinox and winter solstice with the maximum of ionosphere activity.This research also showed that solar flux has strong correlation with TEC with coefficient correlation 0.81